UPAYA PENINGKATAN HASIL PANEN PADI DAN TEMBAKAU MASYARAKAT DESA GAPURA MELALUI PEMANFAATAN KOTORAN KAMBING SEBAGAI BAHAN BAKU PEMBUATAN PUPUK KOMPOS - Wirananda, Muhammad Rifka; Muslimin, Ihwan Nul; Hasbudiana, Anisa; Jufri, Akhmad; Azizah, Alfi; Sagita, Lara; Hilmi, Lubna Tul; Halil, Muhammad; Nurhaliza; Ardianto, Akmal; Mitakasia, Dinda Sesar (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) is a form of community service activities carried out by universities. In KKN activities carried out in Gapura Village, Pujut District, the Mataram University KKN student group carried out various activities with the main target being handling problems in the agricultural sector. Gapura Village is a village where the majority of the population are farmers. Most farmers in this village prefer to use chemical fertilizers rather than organic fertilizers. Most of the farmers in this village also work as livestock breeders. However, people are still unable to manage their livestock waste properly. Therefore, the aim of implementing this KKN activity is to overcome several problems related to community difficulties in obtaining chemical fertilizers such as urea, community dependence on the use of chemical fertilizers which can have a negative impact on crop yields and damage the soil, lack of community knowledge about the use of compost fertilizer, and the community's difficulty in dealing with livestock waste, especially goat manure. There are several methods implemented, namely surveys, training in making fertilizer from goat manure, and socializing the results of compost fertilizer products. The results of this activity are the availability of compost fertilizer as a substitute for chemical fertilizer, utilizing existing goat manure waste and increasing the community's knowledge and skills in processing goat manure into compost, as well as providing more in-depth information to the public regarding the benefits of fertilizer, business potential that can be explored, and The positive impact that can result from using livestock manure as raw material for compost fertilizer.